Evaluation of the adhesive properties of the cornea by means of optical coherence tomography in patients with meibomian gland dysfunction and lacrimal tear deficiency. - Pietro Emanuele Napoli; Franco Coronella; Giovanni Maria Satta; Maria Silvana Galantuomo; Maurizio Fossarello (PLoS ONE, 2014)
The aim was to determine the influence of meibomian gland dysfunction (MGD) and aqueous tear deficiency dry eye (ADDE) on the adhesive properties of the central cornea by means of optical coherence tomography (OCT), and to investigate the relationship between corneal adhesiveness and classical tear tests, as well as the reliability of results, in these lacrimal functional unit disorders.Prospective, case-control study.Twenty-eight patients with MGD and 27 patients with ADDE were studied. A group of 32 healthy subjects of similar age and gender distribution served as a control group. The adhesive properties of the anterior corneal surface were measured by OCT, based on the retention time of adhesion marker above it, in all participants.An excellent (≥5 minutes), borderline (within 3-5 minutes), fair (within 1-3 minutes) and poor (<1 minute) values of corneal adhesiveness were found, respectively, in 0%, 7.1%, 64.3% and 28.6% of MGD, in 0%, 7.4%, 63% and 29.6% of ADDE, and in 31.3%, 65.6%, 3.1% and 0% of healthy patients. The differences in time of corneal adhesiveness between MGD and healthy patients, as well as between ADDE and healthy patients, were found to be statistically significant (p<0.001; p<0.001; respectively). Conversely, no statistical significant differences between MGD and ADDE were found (p = 0.952). Data analysis revealed a statistically significant correlation between corneal adhesiveness and clinical tests of dry eye, as well as an excellent degree of inter-rater reliability and reproducibility for OCT measurements (p<0.001).ADDE and MGD share similar abnormalities on OCT imaging. Decreased adhesive properties of the anterior cornea were identified as a common feature of MGD and ADDE. This simple OCT approach may provide new clues into the mechanism and evaluation of dry eye syndrome.